Oveta Culp Hobby papers - Hobby, Oveta Culp, 1905-1995.
Correspondence, printed matter, and other papers relating to Hobby's work during World War II as chief of the Women's Interest Section of the Bureau of Public Relations in the War Department and as the first director of the Women's Army Auxiliary Corps, renamed Women's Army Corps in 1943.
U.S. secretary of health, education, and welfare; director of Women's Army Corps; newspaper editor and publisher; and businesswoman.
Library of Congress Prints and Photographs Division.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: United States. -- Army. -- Women's Army Auxiliary Corps; United States. -- Army. -- Women's Army Corps; United States. -- War Department. -- Bureau of Public Relations. -- Women's Interest Section; Women in war -- United States; World War, 1939-1945 -- Participation, Female; World War, 1939-1945 -- Women -- United States; Businesswomen; Cabinet officers; Legislators -- Texas; Newspaper editors; Publishers